103k views
3 votes
Simplify the expression

Simplify the expression-example-1
User Scony
by
6.3k points

2 Answers

5 votes

Solution:

Here we use a law of exponent i.e.


{a}^(m) * {a}^(n) = {a}^(m + n) \\ \\

So,

5² × 5³ × 5²


= {5}^(2 + 3 + 2) \\ \\ = {5}^(7) \\ \\ = 78125 \\ \\

Therefore the answer is 78125 or simply 5⁷

Hope it helps you :)

User Shuwei
by
5.7k points
3 votes

Answer:

2500

Explanation:

5×5 ( 5×5×5 - 5×2 )

25 ( 125 - 25 )

25 ( 100)

25 × 100

= 2500

User Bat
by
6.0k points